Thermal model developed of high electron mobility transistor AlGaN-GaN - Azzeddine Farti; Abdelkader Touhami (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The performance of AlGaN-GaN HEMTs is influenced by the self-heating phenomenon, which leads to the power dissipation that is related to the increase of the local temperature of the device. The study of this increasing of the temperature is executed under different parameters, namely, low field mobility, velocity saturation, thermal conductivity of the substrate. A thermal model is developed to study the effect of this phenomenon on the current-voltage characteristics. Among the techniques to minimize the increase in the local temperature, we based on the good choice of the substrate used in the transistor. To highlight this proposal model, we have made a comparable study between the substrates of silicon and sapphire. Our analytical results are in a good agreement with published experimental data.